Dynamic capabilities in digital marketing for SMEs - Bourdy, Théo Georges Raphaël (2024)
In the rapidly changing environment driven by the pandemic and AI advancements, small firms especially face daunting adaptation challenges. Faruk et al. (2021) highlight the accelerated evolution in digital marketing, whereas Teece (2007) stresses the imperative of dynamic capabilities for continual innovation in these firms. Nambisan, Wright, and Feldman (2019) delve into how digital and AI transformations specifically impact small business entrepreneurship, compelling them to leverage these shifts for survival and growth. This backdrop underlines the critical need for small enterprises to develop and maintain dynamic capabilities amidst such volatility. Current research on dynamic marketing capabilities, particularly in the international context, offers significant insights for businesses. Pfajfar, Mitre˛ga, and Shoham (2022) discuss the need for precise conceptualization of international dynamic marketing capabilities (IDMC) to effectively respond to volatile markets. Kim and Lim (2020) demonstrate that small businesses in emerging markets can leverage entrepreneurial orientation and networking capabilities for success in cross-border e-commerce. Ellström et al. (2021) identify key routines that facilitate digital transformation within firms, emphasizing the strategic integration of digital infrastructures. Vu (2020) establishes a link between dynamic, innovation, and entrepreneurial capabilities and the financial and strategic performance of firms, proposing a model for future empirical studies. Finally, Pfajfar et al. (2022) highlight the importance of further exploring dynamic capabilities in international marketing to enhance firm performance. While there is significant research on dynamic marketing capabilities, especially in larger and international firms, less is known about how small firms adapt to digital marketing changes. Specifically, the ways small firms detect market shifts, capitalize on digital opportunities, and manage their digital transformation are not well explored. This gap shows a need for detailed study into the dynamic capabilities that enable small firms to succeed in the digital marketing realm.